Iraq Exports, imports and GDP: The Co-integration and causality for the period (1990-2020) - Dr.Ahmed Hadi Salman (Genius Journals, 2022)
The research aims to identify the causality of exports and imports in the GDP in Iraq, to know the structure of the economic system in Iraq, and the way it works. The importance of the research is that the Iraqi economy is a rentier economy that depends on crude oil, which makes economic relations in its economic system with specific characteristics, so attention must be paid to the revenues of crude oil in order to revive economic activities and promote economic development and overcome obstacles and economic problems resulting from the work of the economic system. Research methodology The time series data of exports, imports and output at fixed prices in local currency for the period (1990- 2020) in Iraq were used, and co-integration and Granger causality were used in order to determine the causal relationship in the research variables. The research concluded that there is no causal relationship, the research recommended reorganizing production relations, by adopting efficiency and high productivity, in order to revitalize the branches of the national economy, promote economic development, and increase economic growth
Keywords: Exports; imports; GDP; rentier economy